A systematic review of medicinal plants and compounds for restoring pancreatic β-cell mass and function in the management of diabetes mellitus - Neha Deora, Krishnan Venkataraman (Journal of Applied Pharmaceutical Science, 2023)
Diabetes mellitus is among the most challenging public health problems worldwide due to its increasing prevalence and its associated complications, affecting individuals, healthcare systems, and economies. Insulin, a crucial hormone for maintaining glucose homeostasis, is secreted by pancreatic β-cells. The progression of both type 1 (T1D) and type 2 (T2D) diabetes is aided by dysfunction/reduced functional β-cell mass, which results in decreased insulin secretion and long-term complications. There has been a surge in interest in drug discovery programs targeted at augmenting both the quality and quantity of pancreatic islets. Several small-molecule drugs and biologics have already been proposed, and newer entities are being investigated. Importantly, plant and plant-derived compounds have a high potential for increasing the number, volume, and functionality of pancreatic islet cells. An update on the current research on the capacity of Aloe vera, Momordica charantia, Tinospora cordifolia, Gymnema Sylvestre, Panax Ginseng, and plant-derived compounds including geniposide, berberine, phenylpropenoic acid glucoside, genistein, naringenin, baicalein, and apigenin to restore β-cell mass and function is given in this systematic review. Since β-cell deficiency is a defining feature of both T1D and T2D, it is critical to comprehend the role of some of these natural products in restoring pancreatic β-cell functionality.
Keywords: Aloe vera, β-cell restoration, diabetes mellitus, Gymnema Sylvestre, Momordica charantia